2012
DOI: 10.1029/2012jc008372
|View full text |Cite
|
Sign up to set email alerts
|

Impact of tropical cyclones on the ocean heat budget in the Bay of Bengal during 1999: 1. Model configuration and evaluation

Abstract: [1] The impacts of two consecutive, strong tropical cyclones (TCs) -04B (10/15-10/19) and 05B (10/25-11/3) in 1999 (hereafter, TC1 and TC2) -on the upper ocean temperature and surface height of the Bay of Bengal (BoB) are examined using the Hybrid Coordinate Ocean Model (HYCOM). The HYCOM control run is driven by the Cross-Calibrated MultiPlatform (CCMP) satellite winds, European Center for Medium-Range Weather Forecasts Re-analysis Interim (ERAI) surface reanalysis data, and Tropical Rainfall Measuring Missio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 105 publications
0
20
0
Order By: Relevance
“…The diffusion/mixing parameters of the model are identical to those used in Wang et al . []. The nonlocal KPP [ Large et al ., ] mixing scheme is used.…”
Section: Model and Experimentsmentioning
confidence: 99%
“…The diffusion/mixing parameters of the model are identical to those used in Wang et al . []. The nonlocal KPP [ Large et al ., ] mixing scheme is used.…”
Section: Model and Experimentsmentioning
confidence: 99%
“…Temperature inversions can have a significant impact on the heat budget of the surface mixed layer, because the mixed layer can be warmed by vertical heat advection, entrainment, or vertical diffusion at its base (Han et al 2001;de Boyer Montégut et al 2007;Wang et al 2012;Girishkumar et al 2013;Akhil et al 2014). On the other hand, some studies based on numerical experiments (Howden and Murtugudde 2001;de Boyer Montégut et al 2007) and observations (Shenoi et al 2002(Shenoi et al , 2005 claimed that the mixed layer heat budget in the Bay of Bengal was mostly dominated by surface heat flux forcing.…”
Section: Introductionmentioning
confidence: 99%
“…Rao et al (2002) suggested that the thick barrier layer prohibited thermocline movement from affecting SST variability along the coast of the bay, but they did not specify what process controlled SST variability. Wang et al (2012) and Girishkumar et al (2013) found nonnegligible influence of temperature inversions on SST. The former was based on numerical experiments with an ocean general circulation model (OGCM) and focused on short-term variability related to the passages of two cyclones; the latter used 11-month records from a moored buoy deployed at the interior of the bay.…”
Section: Introductionmentioning
confidence: 99%
“…To assess the effect of this internal variability on the modeled seasonal and interannual signals, an additional HYCOM experiment is performed (HYCOM_InternalEXP; Table 1). HYCOM_InternalEXP is a finer resolution model run, with 0.25° × 0.25° grid spacing and 30 layers [ Wang et al , 2012], and it is forced by ERA‐Interim monthly climatology [ Dee et al , 2011] and run forward in time for 59 years. The results from years 16–40 are analyzed.…”
Section: Model and Experimentsmentioning
confidence: 99%